Synthesis and activity of nucleoside-based antiprotozoan compounds. Issue 7 (1st April 2017) - Tran, Huu-Anh; Zheng, Zhaoyan; Wen, Xianghui; Manivannan, Srinivasan; Pastor, Arnaud; Kaiser, Marcel; Brun, Reto; Snyder, Floyd F.; Back, Thomas G.
Graphical abstract: Abstract: Parasitic protozoa employ a salvage pathway to synthesize purines and generate essential active nucleotides, whereas mammals are capable of their de novo biosynthesis. This difference provides opportunity for the design of potential new antiprotozoan compounds. A series of 47 adenosine analogues was prepared with modifications at the 2-, 6- and 5′-positions, based on the hypothesis that such compounds would serve as substrates for protozoan nucleoside salvage enzymes, while remaining refractory in mammalian cells. The nucleosides were designed to produce toxic metabolites upon cleavage to the corresponding purine base by the parasite. Three 7-deazaguanosine derivatives were prepared with similar objectives. All of these compounds were tested in vitro against T. brucei (African sleeping sickness), T. cruzi (Chagas' disease), L. donovani (leishmaniasis) and P. falciparum (malaria). In order to determine the therapeutic selectivity indices (SI) of the antiprotozoan nucleosides, their cytotoxicities toward a rat myoblast cell line were also determined. One adenosine derivative proved highly effective against P. falciparum (IC50 = 110 nM and SI = 1010, while a modified guanosine displayed potent activities against L. donovani (IC50 = 60 nM, SI = 2720) and T. brucei (IC50 = 130 nM, SI = 1250), as well as moderate activity against T. cruzi (IC50 = 3.4 µM, SI = 48). These results provide proof of concept for the nucleoside-based antiprotozoan strategy, as well as potential lead compounds for further optimization and validation.